2005
DOI: 10.1103/physrevb.72.174431
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic ordering at the edges of graphitic fragments: Magnetic tail interactions between the edge-localized states

Abstract: To understand the formation mechanism of magnetic moments at the edges of graphitic fragments, we carry out first-principles density-functional calculations for the electronic and magnetic structures of graphitic fragments with various spin and geometric configurations. We find that interedge and interlayer interactions between the localized moments can be explained in terms of interactions between the magnetic tails of the edge-localized states. In addition, the dihydrogenated edge states as well as Fe ad-ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
384
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 524 publications
(417 citation statements)
references
References 25 publications
31
384
2
Order By: Relevance
“…The localized edge states form a two-fold degenerate flat band at the Fermi energy (E F ), existing in about one third of the Brillouin zone away from the zone center 12,13,14,15 . By invoking band ferromagnetism, it has been suggested that an opposite spin orientation across the ribbon between ferromagnetically ordered localized edge states on each edge in ZGNRs is the ground-state spin configuration; that is, the total spin is zero 12,18,19 . Because the states around E F are the edge states and linear combinations of them, the effects of external transverse fields are expected to be significant on these states, in constrast with those on the extended states 20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The localized edge states form a two-fold degenerate flat band at the Fermi energy (E F ), existing in about one third of the Brillouin zone away from the zone center 12,13,14,15 . By invoking band ferromagnetism, it has been suggested that an opposite spin orientation across the ribbon between ferromagnetically ordered localized edge states on each edge in ZGNRs is the ground-state spin configuration; that is, the total spin is zero 12,18,19 . Because the states around E F are the edge states and linear combinations of them, the effects of external transverse fields are expected to be significant on these states, in constrast with those on the extended states 20 .…”
mentioning
confidence: 99%
“…2b) is favored as the ground state over the configuration with same spin orientation between the two edges 12,18,19 . (The present result of antiferromagnetic spin configuration on the honeycomb lattice is consistent with a theorem for electrons on bipartite lattice 23 .)…”
mentioning
confidence: 99%
“…This conclusion is in striking difference from the case of ZZ-GNRs, where the ground electronic state was found to have an AFM spin ordering regardless of the dimensions of the ribbon. [19][20][21][22][23][24][25][26]28,29,42,[45][46][47][48][49][50][51][52] Interestingly, contradicting results have been reported in the literature, 33 indicating that the ground state of unpassivated zigzag CNTs has a low-spin AFM ordering even for nanotubes that have earlier been considered to present a high-spin ferromagnetically ordered ground state. 32 In light of the considerable progress that has been made in the synthesis and fabrication of ultra-short [60][61][62][63][64] and open ended 65 CNTs and ultra-narrow GNRs, [66][67][68][69] it is desirable to obtain a full understanding of their electronic properties.…”
Section: Introductionmentioning
confidence: 93%
“…11 Magnetic effects are expected in the system due to the large state degeneracy at the Fermi level. 9,33,34 The DOS obtained when the electronic spin degree of freedom is included in the calculation is given in Fig. 6.…”
Section: B Characterization Of the Edge Statesmentioning
confidence: 99%
“…8 Calculations for zigzag-edged carbon strips without hydrogen termination indicate that the AFM state is also the lowest-energy state. 9 In contrast, the armchair-edged nanoribbons do not show such magnetic phases due to the delocalized nature of the frontier orbitals. 10 Similar magnetic effects related to the electronic states spatially localized at the zigzag edges have been also predicted for finite graphene nanoislands.…”
Section: Introductionmentioning
confidence: 99%